(untitled) - Ramakrishnan, Raghu (Boston, 1997)
Features of this book include a comprehensive treatment of file organisations and implementation topics; thorough discussion of SQL based on the SQL-92 standard. It also includes all aspects of database design, and explains the relationship of conceptual design, normalization and physical design. Its emphasis is on widely used concepts and techniques.
Keywords: Database mangement